Peran Sosial Perempuan Dalam perspektif Al-Qur’an - Putri Alya Nurhaliza, Riru Rahimah, Sri Lutfiatul Ulfa dan Fajar Syarif (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
This study examines the social role of women in the perspective of the Qur'an. Women are part of Islam and women have an important position in Islam. Islam is very respectful of women, Islam also considers women and men to have the same position. Where Islam strongly recommends education for women, as well as having social roles that are no less important than men, it is proven by the existence of female public figures in the fields of politics, economics, health, and so on. Women also have a role in their families and households, because women are leaders in their households and even complement and need each other. There is no cotomy and role discrimination between men and women. This research shows that women and men have the same rights and roles to actualize themselves in society.